Sharia Constitutionalism: Negotiating State Interests and Islamic Aspirations in Legislating Sharia Economic Law - Bambang Iswanto; Miftah Faried Hadinatha (Universitas Islam Negeri Jakarta, 2023)
Sharia economic law in Indonesia has experienced a significant increase in its role after it was promulgated and implemented as part of the country's legal system. As a country that is neither secular nor Islamic, the incorporation of the Sharia economy into the national legal system has been constitutionally confirmed through various decisions of the Constitutional Court. Therefore, this article examines the decisions of the Constitutional Court regarding the constitutionality of legal norms for halal certificates and halal products, zakat management, and Islamic banking disputes to investigate their implications for ensuring the enforcement of Islamic economic law in Indonesia. This study uses normative legal research, namely the law and case approach, in light of Indonesian discourse on Islam, the state, and the Constitution. It concludes that the Constitutional Court has confirmed the existence of Sharia economic law as part of the national legal system that follows constitutional norms, aka Sharia constitutionalism. The Constitutional Court's decision illustrates a reciprocal relationship between religion and the state that supports the development of Sharia economic law that aligns with the aspirations of Muslims. Abstrak: Hukum ekonomi syariah di Indonesia telah mengalami peningkatan peran yang signifikan setelah diundangkan dan dilaksanakan sebagai bagian dari sistem hukum negara. Sebagai negara yang bukan sekuler maupun Islam, inkorporasi ekonomi syariah ke dalam sistem hukum nasional telah dikukuhkan secara konstitusional melalui berbagai putusan Mahkamah Konstitusi. Artikel ini mengkaji putusan Mahkamah Konstitusi tentang konstitusionalitas norma hukum sertifikat halal dan produk halal, pengelolaan zakat, dan sengketa perbankan syariah untuk menyelidiki implikasinya dalam memastikan penegakan hukum ekonomi syariah di Indonesia. Kajian ini menggunakan penelitian hukum normatif, yaitu pendekatan undang-undang dan kasus, dalam konteks wacana Indonesia tentang Islam, negara, dan konstitusi. Disimpulkan bahwa Mahkamah Konstitusi telah mengukuhkan keberadaan hukum ekonomi syariah sebagai bagian dari sistem hukum nasional yang mengikuti norma konstitusi alias konstitusionalisme syariah. Putusan MK menggambarkan hubungan timbal balik antara agama dan negara yang mendukung pengembangan hukum ekonomi syariah yang sejalan dengan aspirasi umat Islam.